Incremental Effect of Academic Predictors on Nursing Admission Assessment. Issue 6 (November 2018) - Liu, Xin; Codd, Casey; Mills, Christine
Abstract : This study examined the incremental values of academic predictors that may be adopted as nursing school admission criteria. The findings revealed that using additional content areas of mathematics, reading, and English in conjunction with science contributes significantly to the prediction of early nursing school success. This study demonstrates an incremental validity approach that provides valuable guidelines to inform the selection of effective, accurate, and cost-effective admission tools for screening qualified nursing candidates. Abstract : Supplemental digital content is available in the text.